Advertising Billboards are a Source of Pollution and Landscape Transformation in Beautiful Lomé, Togo (Architecture Image Studies, 2026)
Landscaping is one of the factors that makes a space attractive. This research, which identified, quantified, and analyzed 259 signs along the stretch of road between the GTA intersection and the junctions with Boulevard du 13 Janvier in Lomé, reveals a predominance of commercial advertising (54.44%), followed by road signs (20.08%) and informational signs (18.15%). This heavy commercialization of public space, manifested in aggressive strategies at major intersections and crossings through a high density of advertising displays, detracts from the aesthetic appeal and transforms the urban landscape of Lomé, a city that has always been a model of West African cities. This visual saturation not only compromises road safety by creating unavoidable focal points but also distorts the civic function of public spaces by constituting visual nuisances on multiple scales. This study reveals a management deficit and a failure to take into account urban planning regulations. To this end, it is imperative to rebalance public urban space along roads and thoroughfares through appropriate uses, limitations on building sizes, and taxation proportional to the areas affected. Reclaiming shared urban spaces is therefore essential to guaranteeing urban functions, quality of life, safety, aesthetics, and the democratic right to the city.